Study on the Early Hydration of Cement Paste Containing Sodium Chloride - Rahimah, Embong; Kusbiantoro, Andri (Trans Tech Publications, Switzerland, 2014)
This paper studies the effect of sodium chloride as the additive component in cement paste. Sodium chloride was included at 0.5%, 1%, 1.5%, and 2% by weight of cement content. Analysis on the performance of this reagent was conducted via setting time, compressive strength, and porosity test. Based on the setting time analysis, the inclusion of sodium chloride can extend the initial setting time of cement paste up to 24.91% longer than control specimen. Obstruction on the formation of calcium silicate hydrate gel by sodium and chloride ion was one of the possible causes to this phenomenon. Acceleration on the compressive strength development by sodium chloride was also detected. It appears that sodium chloride was able to de-flocculate the coagulated cement particles and reduced the viscosities of cement slurries; hence resulted in faster early hydration process.